MENGENAL KONSEP PENDIDIKAN KARAKTER: SEBUAH TINJAUAN KONSEPTUAL - Lisa Mayang Sari; Ghina Dwi Fadel; Mulyadi; Rivana Valentina; Mutia Puspa Hidayah; Weni Yulastri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education is essentially a dynamic process that focuses not only on intellectual intelligence but also on moral maturity and the formation of noble character. In the modern era, the rapid flow of globalization triggers moral degradation, which poses a real threat to the younger generation if not fortified with a strong spiritual and ethical foundation. This study aims to comprehensively examine the concept, objectives, urgency, and implementation strategies of character education, particularly at the elementary education level. The research method used is a literature review conducted by systematically collecting, analyzing, and synthesizing qualitative data from various books and relevant scientific articles. The results show that character is not a static, innate aspect, but rather a personal quality that can be forged and intentionally changed through appropriate environmental interventions. The implementation of character education targets two main subjects in schools: students and educators. For students, the focus of development is directed towards religious values, honesty, discipline, responsibility, cooperation, and independence. Meanwhile, for educators, strategies for instilling values ​​are implemented through modeling, habituation, curriculum integration, developing a positive school culture, and collaboration with parents. Specifically, at the elementary school level, strengthening independent character and moral development can be realized through digital literacy-based assignments, stimulating independent creativity, and creating classroom learning contracts.